If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n + -4 + -9 = 0 Reorder the terms: -4 + -9 + n = 0 Combine like terms: -4 + -9 = -13 -13 + n = 0 Solving -13 + n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + n = 0 + 13 Combine like terms: -13 + 13 = 0 0 + n = 0 + 13 n = 0 + 13 Combine like terms: 0 + 13 = 13 n = 13 Simplifying n = 13
| -18x-36+36-12x=-14 | | (x-17.7)+19.6=17.8 | | (4X-10)=(X) | | X^2/x+4=16/x+4 | | 7x^3-x^2-56x+8=0 | | 3d+1=-5 | | r^2s^4t^6/r^3s^4t^-6 | | x-5y-25=0 | | 4s-72=2(6-3s)-4s | | (2/x)/(1/2x) | | s/6-6=12 | | (5t^2-t-8)(2t^2+5t-1)= | | 20-0=10o-2 | | 1/2y-1/3(y-1)=5y | | 8+4l=-10+k | | 9x^2-y^2=-16 | | 9x^2-y^2=-16 | | 3x+5y=80 | | (4/5y-3)=(2/3y+4) | | 24x^2+30x=0 | | 2.4/0.39 | | 12.99x=50.50 | | c=k+w/2 | | 5x^2+y^2=30 | | 2x-6+5x=3x+10 | | (3/7n)+(7/3n) | | 6=3x+6/x+1/x | | -2(3x-5)+3x=-2x-10 | | 11r+-12r= | | 4m^2-5m-6= | | 4(3-5x)=5x-188 | | (4x-7)(2x-9)= |